Kinerja Sumber Daya Manusia Generasi Z Meningkatkan Produktivitas Industri Kreatif Digital Monsia Creative - Budi Lestari, Ajeng Prihastuti; Mega Hastuti, Sri Wahyu (Universitas Islam Kadiri, 2025)
Human resources (HR) play a vital role in determining the success of an organization, especially in the rapidly growing digital creative industry. Generation Z, who have grown up in the era of technology and digitalization, possess characteristics that distinguish them from previous generations, such as high technological skills, the ability to adapt quickly, and a tendency to seek meaning in their work. In the context of a creative company like Monsia Creative, which operates in video production, photography, graphic design, and digital marketing, managing the potential of Generation Z is crucial to ensure their contribution to creating innovation and optimal productivity. The performance of Generation Z in this industry is influenced by several factors, such as flexibility in working hours and location, opportunities for skill development, and a supportive work environment. They tend to be more productive and motivated when given freedom in organizing their work and when their contributions are recognized. An inclusive work atmosphere, along with opportunities for personal development, is also essential in boosting employee loyalty and engagement. To maximize the potential of Generation Z, companies like Monsia Creative need to create an environment that fosters creativity, provide continuous training, and manage policies that support a balance between work and personal life to improve their satisfaction and productivity within the company.